Pengaruh Penggunaan Serbuk Kaca Terhadap Karakteristik Marshall Campuran HRS-WC: The Effect Of The Use Of Glass Powder On The Characteristics Of Mixed Marshall HRS-WC - Deani Rahma Almira; Nirwana Puspasari; Norseta Ajie Saputra (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
HRS is a mixture consisting of hard asphalt and coarse, fine aggregate, and filler. One of the wastes that have not been used optimally is glass powder. When viewed physically, glass powder has small particles and, material weight is large enough to complete the requirements as a filler for asphalt mixtures. This study aims to determine the effect of glass powder on marshall characteristics, namely density, stability, VMA, VIM, VFB, flow, and MQ. This research method includes the preparation of materials and tools followed by testing of coarse aggregate, fine aggregate, and filler. After asphalt mix design for marshall testing to obtain the Optimum Asphalt Content (KAO) that will be used for the test object is 9 pieces with a ratio of 25%, 50%, and 75% glass powder filler from a total weight of 3% as a partial replacement of cement in the HRS-WC mixture. The results showed that the flow value of 3.7 mm had completed the requirements for using 50% glass powder filler. The use of 75% glass powder filler produces an MQ value of 369,124 Kg/mm. Whereas VIM and VFB values in the use of a combination of 25%, 50%, 75% glass powder filler don’t comply with the requirements specifications of Bina Marga 2018 revision 2. In general, the glass powder cann’t use as an alternative to cement filler